1999
DOI: 10.1152/ajpheart.1999.276.5.h1520
|View full text |Cite
|
Sign up to set email alerts
|

Wortmannin inhibits insulin-stimulated activation of protein phosphatase 1 in rat cardiomyocytes

Abstract: A major function of insulin in target tissues is the activation of glycogen synthase. Phosphatidylinositol 3-kinase (PI3K) has been implicated in the insulin-induced activation of glycogen synthase, although the true function of this enzyme remains unclear. Data presented here demonstrate that the PI3K inhibitors wortmannin and LY-294002 block the insulin-stimulated activation of protein phosphatase 1 (PP1) in rat ventricular cardiomyocytes. This loss of phosphatase activation mimics that seen in diabetic card… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 40 publications
2
9
0
Order By: Relevance
“…It is thought that the phosphatase PP1 dephosphorylates Thr 495 , and inhibition of PP1 results in the hyperphosphorylation of Thr 495 , thus blunting eNOS activity. There is also evidence that insulin stimulates PP1 activity via a PI3-kinase-dependent pathway in rat cardiomyocytes (6). Interestingly, we observed that, in HUVECs, insulin stimulated PP1 activity, resulting in an increased dephosphorylation of Thr 495 .…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…It is thought that the phosphatase PP1 dephosphorylates Thr 495 , and inhibition of PP1 results in the hyperphosphorylation of Thr 495 , thus blunting eNOS activity. There is also evidence that insulin stimulates PP1 activity via a PI3-kinase-dependent pathway in rat cardiomyocytes (6). Interestingly, we observed that, in HUVECs, insulin stimulated PP1 activity, resulting in an increased dephosphorylation of Thr 495 .…”
Section: Discussionsupporting
confidence: 49%
“…Treatment with calyculin-A prevented the insulin-induced dephosphorylation of Thr 495 (data not shown). Insulin has been shown to activate PP1 via a PI3-kinase-dependent pathway in rat cardiomyocytes (6). Therefore, we tested whether insulin would also increase PP1 activity in HUVECs and whether IL-6 would affect insulin-stimulated PP1 activation.…”
mentioning
confidence: 98%
“…However, PI3K can also control PP1 activity (Ragolia and Begum, 1998;De Luca et al, 1999), suggesting that it can indirectly lead to receptor dephosphorylation. Using several experimental approaches, we identified PP1 as a mediator of TNF␣-dependent GABA A R trafficking in cultured hippocampal neurons and acute hippocampal slice CA1 pyramidal neurons.…”
Section: Discussionmentioning
confidence: 99%
“…In cells, PP1 activity appears to be stimulated in response to insulin and other mitogens (45)(46)(47). Some of these physiological stimuli also lower PP2A activity (48 -53), perhaps contributing to the activation of the mitogen-regulated protein kinases cascade and to the promotion of cell proliferation (27).…”
Section: Pp2amentioning
confidence: 99%